(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
This paper aims to represent the caste-based discrimination and the resistance of marginalized Dalits in the anthology of the poem- Ᾱphar: Unmukta Pustā (Anvil: Liberated Generation). The study has adopted a qualitative research approach employing textual analysis to analyze fourteen selected poems from the anthology, focusing on their portrayal of Dalit discrimination and voices of resistance. Foucault’s insight of ’discourse and counter-discourse’ and Hall’s concept of ’representation’ are applied as theoretical tools to discuss how the poems expose and challenge caste-based hierarchies, untouchable practice, and social exclusion. The finding reveals that the poems depict caste-based discourse as a tool of discrimination against Dalits while simultaneously presenting Dalit voices as a counter-discourse challenging systemic oppression. Through the poems, Dalits question the dominant caste narratives and demand equality. However, their voice is marginalized and often unheard, and they are culturally and politically excluded from society by exclusionary ideologies. In this regard, findings suggest that ongoing counter-discourses, particularly in literature, media, and politics, are essential for addressing caste discrimination and fostering a more inclusive society.